Corporate awards and executive compensation: Empirical evidence from Chinese A-Share listed companies - Bofu Deng; Jiawei Liu; Li Ji (China Journal of Accounting Studies (CJAS), 2020)
From the perspective of non-financial performance, this study investigates the effect of corporate awards on executive compensation. We find that as a measure of non-financial performance, corporate awards help increase executive compensation by demonstrating the company's status in the industry through the efforts of executives. In addition, corporate awards play an important role in supplementing the financial performance of a firm to improve executives' pay-performance sensitivity. Our empirical evidence also reveals that corporate awards are included as a subjective indicator to evaluate the non-financial performance of state-owned enterprises (SOEs) in China: the increase in compensation and the stickiness of this compensation for financial performance based on corporate awards in SOEs are both stronger than in non-SOEs. Moreover, when managers cannot fully obtain other forms of incentives (such as perk consumption or equity incentives), the effect of corporate awards on managers' monetary remuneration is more significant.
Keywords: 650; Corporate awards; nonfinancial performance; executive compensation; pay-performance sensitivity